Book reviews: Vijay Gupta and Michael Th. Rassias, "Computation and Approximation", Springer Cham 2021, Ser.: Springer Briefs in Mathematics DOI: https://doi.org/10.1007/978-3-030-85563-5 - ANDRICA, Dorin (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In the book under review, the authors have treated exponential, semi exponential, integral and hybrid operators, some of which have never been studied in the past due to their complex behavior. The book consists of three chapters. The first chapter presents a systematic list of exponential type operators. Some of these exponential type operators associated with x(1+x)2, x3, 2x3=2 and 2x2 have not been studied in the past in such detail. Hence these operators may attract the interest of researchers who may wish to investigate their properties in greater depth. Furthermore, within this chapter a avor for a possible extension of exponential-type operators to semi-exponential operators has also been indicated.